Clonal divergence and genomic meltdown in prostatic pleomorphic giant cell adenocarcinoma - Ma, Xiaoshi; Chen, Kun; Zhang, Jing; Liu, Liming; Luo, Jiping; Huang, Kaipeng; Zhang, Hongying; Liu, Danni; Gou, Jizhou; Feng, Changyin; Zhao, Xia; Li, Wanying; et al. (Frontiers in Immunology, 2025)
BackgroundPleomorphic giant cell adenocarcinoma (PGCA) of the prostate is a rare, aggressive variant characterized by multinucleated giant cells, sarcomatoid features, and resistance to conventional therapies. Despite its recognition in the WHO 2016 guidelines, the molecular drivers and clinicopathological correlates of PGCA remain poorly characterized. This study presents the first integrative clinicogenomic profiling of PGCA, revealing a novel prognostic gene signature with direct implications for diagnosis and treatment.MethodsWe conducted comprehensive clinicopathological and genomic analyses of a treatment-refractory PGCA case using histology, immunohistochemistry (IHC), whole-exome sequencing (WES), clonal evolution modeling, and multicohort validation. IHC assessed key prostate cancer markers (AR, AMACR, KLK3, PTEN, NKX3-1, VIM), while WES compared somatic alterations in PGCA, adjacent adenocarcinoma, and stromal tissue. Public datasets (prostate_dkfz_2018, prad_tcga, prad_mcspc_mskcc_2020) were used for external validation.ResultsPGCA displayed profound pleomorphism, necrosis, and complete loss of luminal markers (AR/AMACR/KLK3), along with strong vimentin (VIM) expression, consistent with epithelial–mesenchymal transition. WES revealed PGCA-specific mutations enriched in cell-cycle and inflammatory response pathways, distinct from metabolic alterations in the adjacent adenocarcinoma. Clonal evolution analysis showed divergent progression from a shared ancestral clone. Importantly, mutations in ADAMTS7, CDH1, DRD5, MGAT5, and TP53 emerged as a robust five-gene signature predictive of biochemical recurrence, metastasis, and poor survival, validated across multiple independent cohorts.ConclusionOur study provides the first molecular roadmap of prostatic PGCA to date, establishing a novel five-gene prognostic signature and revealing fundamental insights into its pathogenesis through divergent evolution from conventional adenocarcinoma. These insights offer new opportunities for precise diagnosis, prognostic stratification, and targeted therapeutic strategies for this lethal prostate cancer variant.